2017
DOI: 10.3389/fmars.2017.00415
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals and Personal Care Products in Municipal Wastewater and the Marine Receiving Environment Near Victoria Canada

Abstract: Concerns over the fate of pharmaceuticals and personal care products (PPCP) within the environment have been growing with the advent of more precise analytical methods. The discharge of municipal wastewater has been identified as a significant source of these contaminants, particularly where wastewater treatment is minimal. Here we present results from a comprehensive monitoring regime located around Victoria, BC, Canada. Samples were collected between 2009 and 2016 from a variety of sources including marine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Implementation of control measures can rapidly reduce loads coming in our wastewater treatment plants. For example, Krogh, Lyons, and Lowe () and Brose et al () (Brose et al, ; Krogh et al, ) found statistically significant decreases in triclosan and/or triclocarban concentrations in wastewater influent in 2014 compared to previous years, which could be attributed to a policy change by the U.S. FDA affecting the source of these compounds in consumer products. Likewise, Andrade et al () (Andrade et al, ) showed a decrease in brominated diphenyl ether (BDE)‐47 and BDE‐49 concentrations in wastewater influent that could be attributed to the phase‐out of these compounds in manufacturing.…”
Section: Discussionmentioning
confidence: 98%
“…Implementation of control measures can rapidly reduce loads coming in our wastewater treatment plants. For example, Krogh, Lyons, and Lowe () and Brose et al () (Brose et al, ; Krogh et al, ) found statistically significant decreases in triclosan and/or triclocarban concentrations in wastewater influent in 2014 compared to previous years, which could be attributed to a policy change by the U.S. FDA affecting the source of these compounds in consumer products. Likewise, Andrade et al () (Andrade et al, ) showed a decrease in brominated diphenyl ether (BDE)‐47 and BDE‐49 concentrations in wastewater influent that could be attributed to the phase‐out of these compounds in manufacturing.…”
Section: Discussionmentioning
confidence: 98%
“…Municipal wastewaters from domestic and industrial sources can contain a range of different pharmaceuticals and personal care products. Such municipal effluents can be contaminated by the presence of acetaminophen [28]; diclofenac and carbamazepine [29]; ibuprofen, naproxen and triclosan [30]; and hormones [31]. Moreover, wastewater streams were reported to contain not only antibiotics from different classes (β-lactams, sulfonamides, quinolones, tetracyclines, macrolides, etc.…”
Section: Sources Of the Release Of Waste Streams Containing Pharmamentioning
confidence: 99%
“…The authors did not, however, observe any trends in triclosan over the same period. Krogh, Lyons, and Lowe () found statistically significant decreases in triclosan concentrations from 2014 to 2016 at two WRRFs in Canada and a decrease in triclocarban concentrations of one of those two facilities. The concentrations of 10 other detected PPCPs at these facilities were stable over the same time period.…”
Section: Resultsmentioning
confidence: 99%